2006
DOI: 10.4049/jimmunol.177.3.1855
|View full text |Cite
|
Sign up to set email alerts
|

Both CXCR3 and CXCL10/IFN-Inducible Protein 10 Are Required for Resistance to Primary Infection by Dengue Virus

Abstract: We examined the extent to which CXCR3 mediates resistance to dengue infection. Following intracerebral infection with dengue virus, CXCR3-deficient (CXCR3−/−) mice showed significantly higher mortality rates than wild-type (WT) mice; moreover, surviving CXCR3−/− mice, but not WT mice, often developed severe hind-limb paralysis. The brains of CXCR3−/− mice showed higher viral loads than those of WT mice, and quantitative analysis using real-time PCR, flow cytometry, and immunohistochemistry revealed fewer T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 68 publications
7
111
1
1
Order By: Relevance
“…NT_109320, NW_001030791, NT_039339), our analyses would indicate that CXCL10 is the relevant CXCR3 ligand expressed in the CNS during WNV encephalitis in these animals. These results agree with recent studies examining intracranial inoculation with lymphocytic choriomeningtis virus (LCMV) or dengue virus in which both CXCL10 and CXCR3 were determined to be required for the migration of virus-specific, effector T cells into LCMVinfected meninges and into dengue-infected brains (57)(58)(59). Additionally, nonredundant roles for these two chemokines were recently demonstrated in a model of HSV-1 corneal infection in which CXCL9 alone was required for CD4 T cell infiltration into this tissue site (60).…”
Section: Discussionsupporting
confidence: 81%
“…NT_109320, NW_001030791, NT_039339), our analyses would indicate that CXCL10 is the relevant CXCR3 ligand expressed in the CNS during WNV encephalitis in these animals. These results agree with recent studies examining intracranial inoculation with lymphocytic choriomeningtis virus (LCMV) or dengue virus in which both CXCL10 and CXCR3 were determined to be required for the migration of virus-specific, effector T cells into LCMVinfected meninges and into dengue-infected brains (57)(58)(59). Additionally, nonredundant roles for these two chemokines were recently demonstrated in a model of HSV-1 corneal infection in which CXCL9 alone was required for CD4 T cell infiltration into this tissue site (60).…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, IP-10 was the only chemokine significantly induced in YFV-17D-vaccinated individuals (Querec et al, 2009), suggesting an important role for YFV-17D immunogenicity in healthy humans with intact immune responses. It has also been shown that IP-10 contributes to decreased DENV replication in immune-deficient IFN regulatory factor (IRF)-3/ IRF-7 knockout mice (Chen et al, 2013) and IP-10 reduces neurological disease in WNV-or DENV-infected mice (Hsieh et al, 2006;Klein et al, 2005). These findings suggest that chemokines and cytokines such as IP-10 play an important role in the balance between pathogen control and immunopathology, and these proteins may have different activity in neuronal versus non-neuronal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…While these chemokines are not detectable in the healthy brain, their expression is highly upregulated following infection of the CNS with various viruses (2,3,10,21,23,24). Deficiency of CXCR3 has been associated with reduced trafficking to and/or positioning of T cells in the CNS in a number of different virally-induced disease models, such as West Nile virus encephalitis (45), mouse hepatitis virus encephalitis (43), and dengue virus encephalitis (18).…”
Section: Ymphocytic Choriomeningitis Virus (Lcmv) Is a Membermentioning
confidence: 99%